The Relationship Between Mothers' Behavior in Feeding Patterns and Nutritional Nutrition of Toddlers Aged 3-5 Years - Debora Natalia Simamora; Nova Sontry Node Siregar; Fransiska Debataraja; Oknalita Simbolon (Sean Institute, 2026)
Toddlerhood is a period of rapid growth, requiring complete nutritional needs. Fulfillment of toddler nutrition depends on maternal behavior. According to the Humbang Hasundutan Health Profile, the prevalence of toddler nutritional status based on the 2024 Basic Health Research (Riskesda) was 16.8%, with undernutrition at 13.3%, adequate nutrition at 63%, and overnutrition at 6.2%. This descriptive, analytical study with a cross-sectional design aimed to determine the relationship between maternal dietary behavior and the nutritional status of toddlers. This study was conducted in Saitnihuta Village, Doloksanggul District, Humbang Hasundutan Regency in 2025. Sampling was conducted using total sampling, with 54 mothers and 54 toddlers. The instruments used were questionnaires and toddler weight measurements. Primary data were obtained from questionnaires and toddler weight measurements, while secondary data were collected from village reports. The results of the study, using a chi-square test with a significant degree of significance, showed that maternal knowledge was related to toddler nutritional status (p-value > α (0.000 > 0.05), maternal attitudes were related to toddler nutritional status (p-value < α (0.000 < 0.05), and maternal actions were related to toddler nutritional status (p-value < α (0.000 < 0.005). It is hoped that mothers with toddlers will understand good eating patterns for their children and the active role of the community in supporting health services and the role of health workers in providing counseling on toddler nutrition.